Depositional architecture, provenance, and tectonic/eustatic modulation of Miocene submarine fans in the Shikoku Basin: Results from Nankai Trough Seismogenic Zone Experiment. (10th June 2013) - Pickering, Kevin T.; Underwood, Michael B.; Saito, Sanny; Naruse, Hajime; Kutterolf, Steffen; Scudder, Rachel; Park, Jin‐Oh; Moore, Gregory F.; Slagle, Angela
Abstract [1] Seismostratigraphy, coring, and logging while drilling during Integrated Ocean Drilling Program Expeditions 319, 322, and 333 (Sites C0011/C0012) show three Miocene submarine fans in the NE Shikoku Basin, with broadly coeval deposits at Ocean Drilling Program Site 1177 and Deep Sea Drilling Project Site 297 (NW Shikoku Basin). The sediment dispersal patterns have major implications for paleogeographies at that time. The oldest, finer‐grained (Kyushu) fan has sheet‐like geometry; quartz‐rich flows were fed mostly from an ancestral landmass in the East China Sea. During prolonged hemipelagic mud deposition at C0011‐C0012 (~12.2 to 9.1 Ma), sand supply continued at Sites 1177 and 297. Sand delivery to much of the Shikoku Basin halted during a phase of sinistral strike slip to oblique plate motion, after which the Daiichi Zenisu Fan (~9.1 to 8.0 Ma) was fed by submarine channels. The youngest fan (Daini Zenisu; ~8.0 to 7.6 Ma) has sheet‐like geometry with thick‐bedded, coarse‐grained pumiceous sandstones. The pumice fragments were fed from a mixed provenance that included the collision zone of the Izu‐Bonin and Honshu Arcs. The shift from channelized to sheet‐like flows was favored by renewal of relatively rapid northward subduction, which accentuated the trench as a bathymetric depression. Increased sand supply appears to correlate with long‐term eustatic lowstands of sea level. The stratigraphic position and 3‐D geometry of the sandbodies have important implications for subduction‐related processes, including the potential for focused fluid flow and fluid overpressures above and below the plate boundary fault: In sheet‐like sands, pathways for fluid flow have greater horizontal permeability compared with those in channel sands.